Maximum Runoff Of The Flood On Wadis Of Northern Part Of Algeria - Ladjel, M.; Gopchenko, E. D.; Ovcharuk, V. A. (University of Eloued جامعة الوادي, 2014)
Wadis of Algeria are characterized by a very irregular hydrological regime. The question of estimating the maximum flow of wadis is relevant. We propose in this paper a method based on an interpretation of the transformation of surface runoff in streamflow. The technique of account the maximal runoff of flood for the rivers of northern part of Algeria based on the theory of channel isochrones is offered.The realization of this method is performed on the basis of hydrometeorological data standarts.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 01
Keywords: wadis, maximum flow, runoff, streamflow, flood.